Avaliação da aplicabilidade clínica do ultra-som e pontas CVDentus® na cirurgia de levantamento do assoalho do seio maxilar - Vasques, Marco Aurélio Blaz (2007)
Total or parcial teeth loss on posterior area of maxilla alveolar process leads to pneumatization of maxillary sinuses, inducing bone turnover, difficulting rehabilitation through prostheses on implants. The maxillary sinus floor elevation surgery was developed to overcome this problem. The perforation of scheneiderian membrane is the most common complication during maxillary sinus floor elevation procedure, with reported literature incidence between 10% and 44%. The proposition of this work was to analyze the clinical feasibility of polycrystalline diamond burs obtained by CVD (Chemical Vapor Deposition) technique, used in a conventional piezoelectric ultrasound device during the osteotomy of maxillary sinus floor elevation surgery and the possible use of a blunt tip insert in the same ultrasound device to perform the elevation of scheneiderian membrane, verifying the occurrence or non-occurrence of membrane perforation during surgical procedure. The used technique showed to be viable, allowed better operatory visibility; reduction of noise and vibration; bone cut precision, with no harm to soft tissue; little bleeding; non-occurrence of excessive heating in the operated area, non-occurrence of perforation of the scheneiderian membrane during osteotomy and only 1 perforation of the schneiderian membrane at the site of an Underwood septa during the elevation procedure of scheneiderian membrane, among 12 maxillary sinuses submitted to surgery, resulting in 100% of success during the osteotomy and 91,67% clinical success rate of the used techinique.